Effect of flow-independent viscosity on the propagation of Rayleigh wave in porous media. Issue 142 (March 2021) - Chen, Weiyun; Wang, Dan; Mou, Yumin; Zhao, Kai; Chen, Guoxing
Abstract: The propagation characteristics of Rayleigh wave near the surface of fluid-saturated poroviscoelastic medium are investigated in this paper. The effective stress in porous media is defined by the linear viscoelasticity theory based on Biot model and Kelvin-Voigt model. The dispersion equations of Rayleigh wave are derived analytically and then solved numerically to obtain its propagation speed and attenuation coefficient in the poroviscoelastic solid half-space. The effects of relaxation time and viscous coupling on the dispersion and attenuation of the Rayleigh wave as well as the body waves are discussed. The results indicate that the flow-independent viscosity has important influence on the propagation characteristics of Rayleigh waves, compared with the flow-dependent effect of viscous coupling between the pore fluid and solid skeleton. Highlights: Combination of spring-dashpot model with Biot theory for the fluid-saturated poroviscoelastic medium. Comparison between the flow-dependent and flow-independent viscous behaviors. Flow-independent viscosity affects the dispersion and attenuation of the Rayleigh wave. The Rayleigh wave behaves differently in the cases of full and partial saturation.